An integrated approach to the Environmental Monitoring Plan of the Pertuso spring (Upper Valley of Aniene River) - Sappa, Giuseppe; Ferranti, Flavia (Acque Sotterranee - Italian Journal of Groundwater, 2014)
Quantitative assessment of groundwater and surface water is an important tool for sustainable management and protection of these important resources. This paper deals with the design of a multi-disciplinary monitoring plan related to the catchment project of the Pertuso spring, in the Upper Valley of Aniene River, which is going to be exploited to supply an important water network in the South part of Roma district. According to the Legislative Decree 152/2006, as modified by DM 260/2010, any infrastructure design should take in consideration an Environmental Monitoring Plan for the hydrogeological settings of the study area. Thus, the hydrogeological characterization combined with an Environmental Monitoring Plan provides to evaluate the potential adverse environmental impacts due catchment works. For water resources assessment and management, the quantification of groundwater recharge is a preliminary step. As a matter of fact, it has been included the quantitative characterization of the Pertuso spring, in the aim of to protect catchment area, which is directly affect by the natural hydrogeological balance of this aquifer. Thus, a multi-disciplinary monitoring plan has been set up, including quantitative and hydrogeochemical measurements, both for groundwater and surface water of the Upper Valley of Aniene River. The target of this Environmental Monitoring Plan is to set up the background framework on the hydromorphological, physico-chemical and biological properties of water resources in the water basin influenced aim by any potential environmental impact due to the construction activities. The Environmental Monitoring Plan and main features of the monitoring network will be presented in this study.